Differential impact of sickle cell trait on symptomatic and asymptomatic malaria - Eunha Shim; Zhilan Feng; Carlos Castillo-Chavez (Mathematical Biosciences and Engineering)
Individuals who carry the sickle cell trait ($S$-gene) have a greatly reduced risk of experiencing symptomatic malaria infections. However, previous studies suggestthat the sickle cell trait does not protect against acquiring asymptomatic malaria infections, although the proportion of symptomatic infections is up to $50%$ in areas where malaria is endemic. To examine the differential impact of the sickle cell trait on symptomatic and asymptomatic malaria, we developed a mathematical model of malaria transmission that incorporates the evolutionary dynamics of $S$-gene frequency. Our model indicates that the fitness of sickle cell trait is likely to increase with the proportion of symptomatic malaria infections. Our model also shows that control efforts aimed at diminishing the burden of symptomatic malaria are not likely to eradicate malaria in endemic areas, due to the increase in the relative prevalence of asymptomatic infection, the reservoir of malaria. Furthermore, when the prevalence of symptomatic malaria is reduced, both the fitness and frequency of the $S$-gene may decrease. In turn, a decreased frequency of the $S$-gene may eventually increase the overall prevalence of both symptomatic and asymptomatic malaria. Therefore, the control of symptomatic malaria might result in evolutionary repercussions, despite short-term epidemiological benefits.